Risk orientation predicts hypoxic time during difficult airway simulation: a mixed-methods pilot study. (3rd December 2019) - Hayward, Jake; Velmurugiah, Niresha; Duff, Jonathan
Abstract : Personality factors may explain some of the practice variation observed in medicine. In this pilot study, we used simulation to investigate the relationship between risk orientation and airway management. We hypothesised that higher risk tolerance would predict earlier intervention. Ten emergency medicine residents from the University of Alberta participated in a standardised difficult airway simulation. There was a constant rate of oxygen desaturation necessitating eventual airway intervention. A debriefing interview and a risk orientation questionnaire followed. Time of hypoxia prior to intervention was the outcome measure. Audio interview transcripts underwent thematic analysis. Nine participants were included; one did not complete the simulation as instructed. Higher risk tolerance predicted longer hypoxic time prior to intubation (r=0.72, p=0.03). Theme analysis revealed consistent fears regarding patient instability and chances of a failed airway intervention. Patient instability was emphasised more so by those who intervened earlier. We show that personality characteristics influence resuscitation decision-making at an early stage of training. Trainees may therefore be susceptible to certain types of medical error based on their risk aversion. Implications for resident training, care quality and patient safety are discussed.